Establishment of growth kinetics profile and measurement of sulphated glycosaminoglycan (sgag) production in monolayer cultured chondrocytes following qur’anic recitation exposure - Hashim, Rosyafirah; Sha'ban, Munirah; Zainuddin, Zainul Ibrahim (2016)
Objectives/Research Problem: Cartilage is an avascular tissue made of one cell type only which is the chondrocyte. Due to the low mitotic property, the chondrocytes have very limited self-repair capacity. As a result, once the cartilage is injured and left untreated, degeneration changes will precede ageing and can be progressive. Limitation in the currently available treatments is noted. Seeking alternative ways to facilitate the cartilage repair and regeneration have become crucial. This study aims to identify the potential effects of the Qur’anic recitation, particularly Surah Al-Fatihah on the sGAG production in the monolayer cultured chondrocytes derived from rabbit articular cartilage.